LOW-COST FOLDED PATH DIFFERENTIAL OPTICAL ABSORPTION SPECTROSCOPY AS NITROGEN DIOXIDE DETECTOR IN AIR - Arif Fatkhurrahman, Januar
Nitrogen dioxide (NO2) contributes to several impacts both for human health and the environment. Periodical measurement of NO2 at industrial and residential area needs comprehensive and reliable instrumentation; long-interference-free measures with minimum maintenance and re-calibration. Absorption photometry can be used as a direct measurement technique based on specific absorption characteristics of NO2 follow Beer-Lambert law. This research approach a low- cost folded path photometer for measurement NO2 in air. Cheap tubular acrylic used as detection cell with 3D printed framework, make it compact, modular, and flexible design for further development. Evaluation of this design conducted by instrument test responds with NO2. Detection limit (LOD) of the measurement using 2 nm resolution of CCD Spectrometer estimated ~1263 ppb. Measurement deviation compare with gas calibration standard at high concentration (50 ppm) estimated 0.8% and 2.85% at lower concentration (3.5 ppm). Co-location analysis using Griesz Saltzmann method as reference has coefficient correlation of 0.65 and higher coefficient correlation of 0.85 when compared using gas analyzer as equivalent method.